Cover Image, Volume 52, Issue 2. (1st April 2019) - Xue, Changyue; Huang, Qian; Zhang, Tao; Zhao, Dan; Ma, Quanquan; Tian, Taoran; Cai, Xiaoxiao
Abstract : The cover image is based on the Original Article Matrix stiffness regulates arteriovenous differentiation of endothelial progenitor cells during vasculogenesis in nude mice by Changyue Xue et al., https://doi.org/10.1111/cpr.12557 .